The Concept of Sustainability in Smart City Definitions - Toli, Angeliki Maria; Murtagh, Niamh (Frontiers in Built Environment, 2020)
Smart cities have emerged as a possible solution to sustainability problems deriving from rapid urbanization. They are considered imperative for a sustainable future. Despite their recent popularity, the literature reveals the lack of conceptual clarity around the term of smart city, due to the plethora of existing definitions. This comprehensive literature review has identified 43 smart city definitions assessed according to the dimensions of sustainability that they consider, environmental, economic or social, and the priority in which they accord the concept of sustainability. The study revealed the common and opposite characteristics of the definitions according to the sustainability dimensions they consider and discussed the limitations they present. Such limitations appear to be related to citizen accessibility, misrepresentation and the particularity of existing urban fabrics. Taking into account these issues, as well as the difference between the smart city vision and its actual implementation, a new updated definition is proposed. The findings of the present study contribute to knowledge and practice by aiding conceptual clarity and, in particular, by drawing attention to underlying assumptions about the role of sustainability in smart city development.